ZIGBEE-BASED DATA ACQUISITION SYSTEM FOR ORNAMENTAL PLANTS - Elisa, Nurul; Putra, Leonardus Sandy Ade; Marpaung, Jannus (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2026)
Ornamental plants require adequate soil moisture to grow optimally. However, manual irrigation is often performed irregularly, resulting in either insufficient or excessive water supply. This study aims to design and implement a ZigBee-based data acquisition system for monitoring ornamental plants and controlling irrigation automatically. The system employs a soil moisture sensor and a DS18B20 temperature sensor, an Arduino Nano as the transmitter controller, an XBee Series 2 module for ZigBee communication, an ESP32 as the receiver controller and Internet gateway, and the Blynk application for real-time monitoring. The system was tested on two potted ornamental plants, while ZigBee communication performance was evaluated at distances ranging from 20 to 120 meters using the Received Signal Strength Indicator (RSSI), packet delay, and Packet Loss as performance parameters. The results show that the system is capable of monitoring temperature and soil moisture, displaying real-time data on the Blynk application, and automatically activating irrigation based on the predefined soil moisture threshold. ZigBee communication was successfully maintained up to 120 meters, with RSSI values ranging from 75.14% to 43.08%, packet delay ranging from 456 to 4663 ms, and a maximum Packet Loss of 43.6%. These results indicate that the proposed system is effective for automatic monitoring and irrigation of ornamental plants, although the communication performance decreases as the transmission distance increases.